PERTIMBANGAN HAKIM DALAM MENENTUKAN HUKUMAN KEPADA PELAKU TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK DALAM PUTUSAN NOMOR 80/PID.SUS/2023/PN.KPG DI PENGADILAN NEGERI KELAS 1A KUPANG - Jaman, Christoffer Markus; Asa, Simplexius; Resopijani, A (Petitum Law Journal, 2024)
The judge's consideration is very important aspect in determining the realisation of the value of a decision that contains elements of justice in the court, legal certainty and contains benefits for the parties concerned so that it must be addressed properly, carefully and carefully. The formulation of the problems in this study are: (1) How are the judges' considerations in determining the punishment for the perpetrator of the crime of sexual intercourse with a child in Decision No.80/Pid.sus/2023/PN.Kpg? (2) What are the factors that influence the sentencing decision in Decision No.80/Pid.sus/2023/PN.Kpg? This research is normative research, namely legal research that examines documents using legislation, court decisions, legal theories, and can be in the form of scholars' opinions. The results of the research conducted by analysing the decision No.80/Pid.Sus/2023/PN.Kpg of the suspect on behalf of Leo Luha Djami Kale: (1) The judge considered that the defendant was proven to have committed a criminal act in accordance with Article 81 paragraph (1) of the Child Protection Law. However, the judge imposed a sentence below the minimum. (2) Based on juridical factors, the judge stated that the defendant's actions had fulfilled the elements of the article in Article 81 paragraph (1) of the Child Protection Law that had been charged against him and based on non-juridical factors that there had been peace between the two families in accordance with Supreme Court Circular Letter No. 1 of 2017 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2017 as Guidelines for the Implementation of Duties for Courts.